2014
DOI: 10.1111/cea.12332
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota and its role in the development of allergic disease: a wider perspective

Abstract: Summary The gut microbiota are critical in the homoeostasis of multiple interconnected host metabolic and immune networks. If early microbial colonization is delayed, the gut‐associated lymphoid tissues (GALT) fail to develop, leading to persistent immune dysregulation in mice. Microbial colonization has also been proposed as a major driver for the normal age‐related maturation of both Th1 and T regulatory (Treg) pathways that appear important in suppressing early propensity for Th2 allergic responses. There i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
199
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 183 publications
(209 citation statements)
references
References 150 publications
(208 reference statements)
3
199
0
7
Order By: Relevance
“…More recently, it has been shown that the diversity of colonization is crucial for the development of an immunoregulatory network that protects against IgE induction in the mucosa 23 . It remains unclear if such a "window" exists also in humans, but this is nonetheless consistent with observations that gut microbial exposures in infancy may impact the maturation of mucosal and systemic immune responses in infants 8,24,25 .…”
Section: Gut Microbiota Are Essential For Normal Development and Regumentioning
confidence: 63%
See 4 more Smart Citations
“…More recently, it has been shown that the diversity of colonization is crucial for the development of an immunoregulatory network that protects against IgE induction in the mucosa 23 . It remains unclear if such a "window" exists also in humans, but this is nonetheless consistent with observations that gut microbial exposures in infancy may impact the maturation of mucosal and systemic immune responses in infants 8,24,25 .…”
Section: Gut Microbiota Are Essential For Normal Development and Regumentioning
confidence: 63%
“…The critical role of the gut microbiota in immune development has been well documented in germ free animal models, demonstrating the failure of normal maturation and, in particular, failure of the systemic immune regulatory networks, that result in both allergic and autoimmune phenomena (as reviewed by) [5][6][7][8] . Significantly, early experiments clearly demonstrated a critical early developmental "window" during which microbial colonization could induce appropriate maturation of the Th2 response and IgE regulation, and after which this was no longer possible 22 .…”
Section: Gut Microbiota Are Essential For Normal Development and Regumentioning
confidence: 99%
See 3 more Smart Citations